2005
DOI: 10.1258/rsmvasc.13.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Coiling of the Brachial Artery: An Uncommon Cause of Difficult Thrombectomy

Abstract: Coiling (or looping) of the artery is a rare morphologic entity, most frequently described in the internal carotid artery. In other arteries, coiling is rarely reported because it remains asymptomatic and without clinical relevance unless inadvertently injured, as for diagnostic or monitoring purposes. We present a case of an unusually difficult thrombectomy of the brachial artery after occlusion following withdrawal of the arterial cannula placed for monitoring during cardiac surgery owing to coiling of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Coiling is frequently described in the internal carotid artery as a cause of cerebrovascular insufficiency or is connected with carotid atherosclerosis. Coiling of the other arteries is rarely reported [ 2 ]. The first clinical report of BA coiling have been described by Casten and Forman in 1962 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coiling is frequently described in the internal carotid artery as a cause of cerebrovascular insufficiency or is connected with carotid atherosclerosis. Coiling of the other arteries is rarely reported [ 2 ]. The first clinical report of BA coiling have been described by Casten and Forman in 1962 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical report of BA coiling have been described by Casten and Forman in 1962 [ 5 ]. According to Ilijevski, et al [ 2 ] this anomaly is seldom reported because it commonly remains asymptomatic. The variant artery is reported in cases of iatrogenic injury, occlusion, or is found accidentally in cases of angiography for monitoring purposes.…”
Section: Discussionmentioning
confidence: 99%
“…2 In other arteries, coiling is rarely reported because it is usually asymptomatic and of little clinical importance. 3 We report an unusual case of coiling of almost 360° in the right external iliac artery in a patient with a 2-month history of an ischemic ulcer on the right toe. To our knowledge, no other cases of coiling or kinking of the iliac arteries as a cause of ischemic ulcers of the legs have ever been described.…”
Section: Introductionmentioning
confidence: 93%